2018
DOI: 10.1002/bmb.21185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of lactase in lactose intolerance supplements

Abstract: Lactase is the enzyme responsible for the digestion of the disaccharide lactose, and deficiency in this enzyme causes the prevalent medical condition lactose intolerance. Management of lactose intolerance can be achieved through the administration of lactase supplements. Lactase is an appropriate platform for advanced enzymatic study because its medical application is a motivator for student learning. The following is an upper‐level biochemistry laboratory sequence that integrates student inquiry and exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Despite the pharmaceutical and commercial relevance of the lactase containing products [ 19 ], our knowledge is limited about the relationship between their structure and activity. In the present study we will use a combination of analytical tools in order to discover structural changes caused by stress conditions, which influence enzyme activity and function.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the pharmaceutical and commercial relevance of the lactase containing products [ 19 ], our knowledge is limited about the relationship between their structure and activity. In the present study we will use a combination of analytical tools in order to discover structural changes caused by stress conditions, which influence enzyme activity and function.…”
Section: Introductionmentioning
confidence: 99%
“…Lactase, also known as β-galactosidase, is one of the important functions of enzymes of the intestinal tract, mainly composed of small intestinal villus and intestinal bacteria secrete of brush border, and closely associated with diarrhea, abdominal distention [ 33 ], and studies have shown that, when the body lacks lactase, the symptoms of lactose intolerance occurs [ 34 ], such as severe diarrhea, abdominal distension [ 32 ], and severe cases can produce dehydration, acidosis and growth disorder, etc. [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some tasks give students opportunities to explore real-world applications of chemistry in fields ranging from healthcare to engineering. , Other teaching methods highlight the interplay between the disciplines. Strategies such as these promote curiosity and immersion into the subject matter, allowing students to practice genuine scientific investigation through engaging in activities where outcomes are unknown. Educators and researchers hold that this approach greatly enhances the pedagogical value of laboratory exercises because (1) it allows for greater discovery beyond that attributed to the “cookbook experience” of traditional laboratories and (2) it facilitates greater collaboration between students and interaction between students and their instructors, thus enhancing the students’ postsecondary experience . These pedagogies have many well-documented successes: learning activities involving inquiry, guided or open, and real-world applications produce greater effectiveness in learning. ,,, It should not be of any surprise, then, that many postsecondary institutions have already adopted an inquiry-based approach in face-to-face learning.…”
Section: Introductionmentioning
confidence: 99%